The effect of low water on loading capacity of inland ships - Dorsser, Cornelis van; Vinke, Frederik; Hekkenberg, Robert; Koningsveld, Mark van (European Journal of Transport and Infrastructure Research, 2020)
Temporary low water levels can have a major impact on the loading capacity of inland ships, and as a consequence on the transport capacity of the overall waterborne supply chain. Insight in the capacity reducing effect of temporarily lowered water levels is important for the design and operation of robust transport chains on the one hand, and for the optimisation of fairway maintenance and long-term infrastructure development on the other. Knowledge on the effects of low water is clearly available at the level of individual ship owners, who adapt their transport operations to changing environmental circumstances, but less accessible at an aggregated level to assess the effects on the overall transport capacity of an inland waterway network. Based on a range of field observations and information collected from individual ships, this article introduces a general model to define the effect of low water constraints on the deadweight capacity and payload of inland ships, for which only the type, length, and beam of the vessel serve as input.